TINGKAT KEPUASAN PASIEN RAWAT INAP BPJS KESEHATAN KELAS III TERHADAP PELAYANAN DI RUMAH SAKIT AVICENNA BIREUEN - Meri Lidiawati; Raihan Utari (Jurnal Sains Riset, 2021)
Hospital according to the WHO Expert Committee on Medical Care Organizations A comprehensive part of a medical organization that functions to provide comprehensive health services to the community, both curative and rehabilitative. In the era of Jaminan Kesehatan Nasional (JKN), all Indonesian people registered through the Badan Penyelenggaran Jaminan Sosial (BPJS) are entitled to health services. This is the Indonesian government's effort to take care of the health rights of each individual Indonesian society. The purpose of this study was to determine the level of satisfaction of the class III BPJS inpatients at Avicenna Bireuen Hospital. The research method used is quantitative quantitative with cross sectional approach. After data analysis, it was obtained that the most respondents were satisfied (89.2%) based on the direct evidence dimension. Satisfied (82.8%) based on the reliability dimension. Satisfied (79.6%) based on the responsiveness dimension. Satisfied (88.2%) based on the proof of guarantee dimension. Satisfied (73.1%) based on the dimensions of evidence of empathy. The highest respondent in the world who is satisfied (83.9%) with the level of patient satisfaction at Avicenna Hospital, Bireuen District.Keywords: BPJS, Satisfaction Level, Hospital